2021
DOI: 10.3389/fcvm.2021.663864
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Non-invasive Cardiac Imaging Assessment in Coronavirus Disease 2019

Abstract: Coronavirus disease 2019 (COVID-19) was initially regarded as a disease of the lungs, which manifests as an acute respiratory illness and pneumonia, although more recently cardiac complications have been well-characterised. Serological cardiac biomarkers have been used to define acute myocardial injury, with significant elevation of high-sensitivity cardiac troponin (hs-cTn) associated with poor prognosis. Accordingly, 20–25% patients with acute myocardial injury (as defined by an elevated hs-cTn greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Therefore, it is necessary to study the long-term consequences on the cardiac function of patients infected with SARS-CoV-2 [ 6 , 7 ]. Transthoracic echocardiography (TTE) remains an important imaging modality used for assessing cardiac function, which can provide relevant information that may impact clinical management for those infected with SARS-CoV-2 [ 8 ]. Left ventricular global longitudinal strain (LVGLS), measured by speckle tracking echocardiography (STE), provides a way to quantify myocardial deformation independent of left ventricular ejection fraction (LVEF) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to study the long-term consequences on the cardiac function of patients infected with SARS-CoV-2 [ 6 , 7 ]. Transthoracic echocardiography (TTE) remains an important imaging modality used for assessing cardiac function, which can provide relevant information that may impact clinical management for those infected with SARS-CoV-2 [ 8 ]. Left ventricular global longitudinal strain (LVGLS), measured by speckle tracking echocardiography (STE), provides a way to quantify myocardial deformation independent of left ventricular ejection fraction (LVEF) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, 84% of positive CMR patients were symptomatic, compared to only half of the patients with negative CMR (28) . In addition, although LV diastolic dysfunction was more in post-COVID-19 patients, previous studies (12,29) showed concomitant RV diastolic dysfunction that could be explained by ventricular interdependence (30) . Previous studies on mild COVID-19 cases showed that RV diameters and systolic function were usually within the normal range despite evidence of myocardial injury (16)(17) .…”
Section: Discussionmentioning
confidence: 84%
“…Since the physicians have obtained data about cardiac involvement during the COVID-19 acute phase, several studies with cardiac imaging have been carried out to determine different markers to guide the decision-making process and understand this disease's cardiovascular evolution. Echocardiography and cardiac magnetic resonance (CMR) were the most explored techniques [58,59]. The main findings of both imaging techniques are summarized in Figure 3.…”
Section: Cardiac Imaging Findingsmentioning
confidence: 99%
“…One of the main findings in echocardiographic studies is the right ventricle (RV) impairment. The pathophysiology of COVID-19 with an important incidence of ARDS can lead to the development of RV dysfunction due to the increased pulmonary microvascular resistance, accompanied by microvascular thrombi, high rate of PE, and even due to mechanical ventilation itself [58,59]. Manzur-Sandoval et al found a high frequency of echocardiographic signs of RV dysfunction (reduced fractional shortening, reduced tricuspid annular plane systolic excursion, and RV dilatation) in patients who required hospital admission.…”
Section: Echocardiographymentioning
confidence: 99%